2008
DOI: 10.1111/j.1365-313x.2008.03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐generation inheritance of methylation patterns in a tobacco transgene following a post‐transcriptional silencing event

Abstract: SummaryWe have studied the inheritance of the epigenetic state of tobacco transgenes whose expression was posttranscriptionally silenced by an invertedly repeated silencer locus. We show that, in hybrids, the coding region of the target neomycin phosphotransferase (nptII) gene was almost exclusively methylated at CG configurations, and dense non-CG methylation occurred in the 3¢ untranslated region. Homologous sequences in the silencer locus were heavily methylated at both CG and non-CG motifs. After segregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
(136 reference statements)
1
21
0
1
Order By: Relevance
“…Notably, this maintenance of methylation was not associated with histone H3 dimethylation and/or H3 acetylation (41). These data were in agreement with observations made in other systems (42), and they clearly showed that transgenic coding/ transcribed regions can also retain CG methylation in the absence of RdDM guide molecules.…”
Section: Maintenance Of Cg Methylationsupporting
confidence: 86%
“…Notably, this maintenance of methylation was not associated with histone H3 dimethylation and/or H3 acetylation (41). These data were in agreement with observations made in other systems (42), and they clearly showed that transgenic coding/ transcribed regions can also retain CG methylation in the absence of RdDM guide molecules.…”
Section: Maintenance Of Cg Methylationsupporting
confidence: 86%
“…Variable maintenance of methylation and contradictory results of previous reports (Jones et al 2001;Lunerova-Bedrichova et al 2008), argue for a model of a sequence-specific mechanism for maintenance of RdDM. Homogeneous/heterogenous distribution of cytosines and/or high/low GC-context all may account for this variation.…”
Section: Discussionmentioning
confidence: 74%
“…However, in contrast to promoter regions, coding region methylation was thought to be meiotically lost in the absence of an RdDM trigger (Jones et al 2001). Nevertheless, in a recent study, CG methylation was maintained in a transgene coding region (Lunerova-Bedrichova et al 2008). Here, besides CG, we observed maintenance also of CHG methylation.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the CG hypomethylation elicited with increased concentration of the drug remained stably inherited throughout plant development and could potentially influence developmental processes. As a consequence, the CG epialleles could be more stable than those of non-CG (Lunerova-Bedrichova et al 2008). However, this may not be absolute since a stable non-CG epiallele (SUP) rescued from the hypomethylated background was reported in Arabidopsis (Jacobsen and Meyerowitz 1997).…”
Section: Heritable Changes In Dna Methylation After the Sah-hydrolasementioning
confidence: 95%